1997
DOI: 10.1097/00005344-199706000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Isoprostanes (8-Iso-Prostaglandin F2α and E2) in Isolated Guinea Pig Hearts

Abstract: Isoprostanes are a family of prostaglandin-related compounds formed from arachidonic acid in a cyclooxygenase-independent manner as products of free radical-initiated lipid peroxidation. To elucidate the biological activity of the F2-and E2-isoprostanes, 8-iso-prostaglandin F2alpha (8-iso-PGF2alpha) and 8-iso-prostaglandin E2 (8-iso-PGE2), we measured hemodynamic effects in isolated perfused guinea pig hearts after cumulative administration (3 x 10(-9)-10(-5) M) of these compounds into the coronary system. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 22 publications
3
48
0
4
Order By: Relevance
“…This cardiac potentiating property of PGE 2 is consistent with those elicited by PGE 2 or its precursor arachidonic acid reported at the whole animal or multicellular myocardial levels [6,9,11]. The PGE 2 -elicited positive cardiac contractile response is expected to counter-balance the vasoconstrictive action of PGE 2 on main arteries such as aorta to facilitate cardiac energy expenditure and ventricular performance [3,12]. The enhanced cardiac contractility in isolated ventricular myocytes is also consistent with the PGE 2 -elicited protection against myocardial dysfunction due to free radical generation [13].…”
Section: Discussionsupporting
confidence: 75%
“…This cardiac potentiating property of PGE 2 is consistent with those elicited by PGE 2 or its precursor arachidonic acid reported at the whole animal or multicellular myocardial levels [6,9,11]. The PGE 2 -elicited positive cardiac contractile response is expected to counter-balance the vasoconstrictive action of PGE 2 on main arteries such as aorta to facilitate cardiac energy expenditure and ventricular performance [3,12]. The enhanced cardiac contractility in isolated ventricular myocytes is also consistent with the PGE 2 -elicited protection against myocardial dysfunction due to free radical generation [13].…”
Section: Discussionsupporting
confidence: 75%
“…12 While the effects of ROS are largely compartmentalized within cells, they trigger generation of stable diffusible lipid peroxidation products like 15-F 2t -isoprostane, a coronary artery vasoconstrictor implicated in the development of postoperative ventricular dysfunction. 19,26 We attribute our findings to patient characteristics, surgical conditions, and study interventions that differ from prior studies. We studied higher risk patients undergoing normothermic CPB and blood cardioplegic arrest.…”
Section: Discussionmentioning
confidence: 85%
“…It exacerbates myocardial IRI, producing left ventricular dysfunction directly via receptor-induced coronary artery vasoconstriction. 19 Furthermore, we previously found that propofol upregulates anti-apoptotic B-cell lymphoma 2 (Bcl-2) gene and protein expression in cardiomyoblasts, allowing them to withstand subsequent oxidative challenge. 20 B-cell lymphoma 2 sequesters pro-apoptotic BAX, a protein that promotes mitochondrial pore opening.…”
Section: Résumémentioning
confidence: 99%
“…In particular, 8-iso-PGE 2 , 8-iso-PGE 1 , and 8-iso-PGF 2␣ were the most potent, with negative log EC 50 (half-maximally effective concentrations) of 6.9 Ϯ 0.1, 6.6 Ϯ 0.1, and 6.3 Ϯ 0.1, respectively. These excitatory effects of isoprostanes have been examined in detail in numerous vascular beds (Janssen, 2001) including the coronary artery (Mobert et al, 1997;Kromer and Tippins, 1999) and have been shown to involve TP receptors: we did not characterize these effects any further in this study.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many reports of the excitatory actions of isoprostanes and the receptor-effector coupling pathways underlying them in vascular, airway and gastrointestinal smooth muscles (Janssen, 2001;Mobert et al, 1997;Kromer and Tippins, 1999;Janssen et al, 2000Janssen et al, , 2001. However, their inhibitory effects on smooth muscle have been largely unexplored: only two groups have described their relaxant effects in pulmonary vasculature (Jourdan et al, 1997;Janssen et al, 2001) and airway smooth muscle (Janssen et al, 2000), and none have examined the signaling pathways involved.…”
Section: Discussionmentioning
confidence: 99%